Classification and positioning of TQM practices for implementation in steel industries: An AHP approach. Issue 9 (1st August 2019) - Bajaj, Shweta; Garg, Ruchi; Sethi, Monika; Dey, Sujit
Abstract : Purpose: The purpose of this paper is to classify the total quality management (TQM) practices and position them based on their importance in the implementation of TQM in steel industries for obtaining improved business performance and customer satisfaction. Design/methodology/approach: The study undergoes a deep literature review to recognise the TQM practices necessary for the implementation of TQM in the steel industry. The identified 17 practices were grouped under three activities such as "breakthrough activities", "improvement activities" and "routine operational and maintenance activities" with experts' suggestion. The positioning of 17 TQM practices and 3 activities of TQM was done using an analytical hierarchy process (AHP) technique as per their relevance in TQM implementation. Findings: The findings of the research show that though all the 17 practices and 3 activities of TQM play a vital role in the successful implementation of TQM in steel industries, breakthrough activities have gained more weightage as compared to the other two activities. Top management commitment, quality system and continuous improvement are relatively more important than the other practices. Research limitations/implications: The research has limitation analogous to the AHP technique. The technique considers all the sub-sets of each nod to be independent from each other, whereas in real world this does not stand true. Practical implications: The study positions the TQM practices and activities on the basis of their relevance in TQM implementation in the steel industry, thus helping the managers in understanding which practice has to give how much importance for TQM implementation in steel industries. By following the practices according to the weights, the managers can achieve the results desired from TQM implementation. Originality/value: The study gives the implementation priorities of TQM practices in the steel industry. To the best knowledge of researcher, it is the first study in the steel sector for TQM implementation. The lacuna was reported by the literature, and the researcher has made an attempt to fill that gap.